CO2 removal in tray tower by using AAILs activated MDEA aqueous solution. (15th October 2018) - Zhang, Pan; Tian, XiangFeng; Fu, Dong
Abstract: A tray tower was designed to verify the absorption performance of CO2 in 1-butyl-3-methylimidazolium glycinate ([Bmim][Gly]), 1-butyl-3-methylimidazolium lysinate ([Bmim][Lys]) and tetramethylammonium glycinate ([N1111 ][Gly]) activated MDEA ( N -methyldiethanolamine) aqueous solutions. The simulated flue gas was composed of 15% (mole fraction) CO2 and 85% N2 and the experiments were performed at 313.2 K. To find a suitable absorbent composition, the mass fractions of MDEA and amino acid ionic liquids (AAILs) respectively ranged from 0.200 to 0.400 and 0.025 to 0.100. The removal efficiency of CO2 ( η CO 2 ) and the overall volumetric mass transfer coefficient ( K G a v ) were determined. The effects of absorbent composition ( w ), absorbent flow rate ( L ), gas flow rate ( G ) and plate number ( N p ) on η CO 2 and K G a v were demonstrated. Our results showed that, when activated by AAILs, MDEA aqueous solution was able to absorb CO2 in tray tower efficiently, and both η CO 2 and K G a v were significantly increased, e.g., in the case of w MDEA  = 0.200, η CO 2 and K G a v were increased from 43.48% to 95.55% and from 0.0069 (kmol m −3  h −1 ·kPa −1 ) to 0.0350 (kmol m −3  h −1 ·kPa −1 ), respectively, when w [N1111][Gly] was changed from 0 to 0.100, indicating AAILs activated MDEA aqueous solution is of great potential for industrial application in CO2 capture process. Highlights: A tray tower was designed to separate CO2 by using AAIL-MDEA aqueous solution. The measured CO2 removal efficiency was higher than the commercial requirements. The overall volumetric mass transfer coefficient in tray tower was determined. Effects of absorbent composition, flow rate and plate number were demonstrated. AAIL activated MDEA aqueous solutions have good application prospect in CO2 removal.